PELUANG PENGEMBANGAN UMKM MANISAN KURMA TOMAT DI KABUPATEN LUMAJANG - Saadillah, Dinu; Nadhirah, Aulia; Al Ardi, Aditya Nizar (Universitas Galuh, 2023)
ABSTRACTTomatoes are one of the fruit commodities that can grow in the lowlands and highlands. However, the high water content makes tomatoes unable to last for a long time. Therefore, it is necessary to diversify tomatoes in order to have a higher selling value. One way of handling it is by processing tomatoes into dried candied fruits. Candied tomatoes in the form of dates at one of the UKM Kurmat (tomato dates) located in Lumajang Regency is a relatively new product so that it can provide a new alternative in creating business opportunities. The development of the candied tomato business in UMKM faces various obstacles. An appropriate business development strategy is needed through strategic planning to face intense competition. The results of the analysis using SWOT (Strengths, Weaknesses, Opportunities and Threats) on tomato date SMEs in Lumajang Regency show that this candied tomato business has been able to make good use of its strengths even though there are still some weaknesses. Capital is a factor that must be considered so that the business can develop properly. In addition, the threats faced by candied dates are more dominant than the opportunities that exist, namely the wider market reach of competitors so that the results of the SWOT analysis indicate that a business development strategy is needed in the form of supporting a diversification strategy or an ST (Strength and Threats) strategy in the form of implementing drying in accordance with GMP standards, analyzing risk management appropriately to avoid losses due to rising prices of supporting materials, applying appropriate promotional tools and attracting consumer interest, prioritizing the competitive advantages of products owned as a promotional event.